2018
DOI: 10.1142/s0219649218500247
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Asymmetries and Service Management: Three Case Studies

Abstract: The purpose of this paper is to investigate how information systems are used by knowledge-intensive service firms and identify their effects on client–provider interactions. The paper uses data from case studies of service-related departments of three multinational firms. We identified several broad trends present in all three case companies. The required degree of knowledge specialisation, coupled with the ability to leverage knowledge created during service interactions resulted in high degrees of knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
(131 reference statements)
0
2
0
1
Order By: Relevance
“…Rather than supporting interaction between service supplier and customer (Payne et al , 2008; Carlborg and Kindstrom, 2014; Gronroos, 2011), ICTs involved limited interaction concurring with previous research (Glushko and Nomorosa, 2013; Paluch, 2014) that interpersonal interaction was replaced by ICTs, that did not support customer relationship building (Rust and Miu, 2006; Rust and Huang, 2014). A possible reason for this is that knowledge asymmetries (Walsh and O'brien, 2018) may exist with service providers possessing more knowledge about requirements than their clients.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than supporting interaction between service supplier and customer (Payne et al , 2008; Carlborg and Kindstrom, 2014; Gronroos, 2011), ICTs involved limited interaction concurring with previous research (Glushko and Nomorosa, 2013; Paluch, 2014) that interpersonal interaction was replaced by ICTs, that did not support customer relationship building (Rust and Miu, 2006; Rust and Huang, 2014). A possible reason for this is that knowledge asymmetries (Walsh and O'brien, 2018) may exist with service providers possessing more knowledge about requirements than their clients.…”
Section: Discussionmentioning
confidence: 99%
“…It is important that as well as being cognisant of local perspectives, NGOs articulate indigenous knowledge (Athayde et al, 2016) though southern NGOs have been found to lack the skills needed to document local knowledge. Nonetheless, the dominant view is of top-down knowledge transfer (Moschitz et al, 2015).It is also important to mitigate the risk of knowledge asymmetries reducing opportunities for knowledge co-creation (Walsh & O'Brien, 2018). The best place to develop solutions is in the context in which they will be implemented (Chambers & Ramalingam, 2016).…”
Section: Background Literature Knowledge Management Dynamics In Inter...mentioning
confidence: 99%
“…Um modelo que leva em consideração aspectos substanciais do que os estudos em gestão do conhecimento têm apresentado é proposto por Gold, Malhotra e Segars (2001), no qual estende elementos teóricos de gestão do conhecimento a uma dimensão programática, denominada 'efetividade organizacional' que é dada em função de duas capacidades organizacionais: 'infraestrutura do conhecimento' e 'processos do conhecimento'. A primeira é composta por elementos tecnológicos (LOON, 2019;WALSH;O'BRIEN, 2018;NEVES, et al, 2018), como sistemas de informação, comunicação, colaboração e, inteligência de negócios; culturais (COOPER, et al, 2016;RICE;HEINZ; VAN ZOONEN, 2019), tais como interação entre pessoas, visão corporativa, sistema de valores e; estruturais (LUPTON;BEAMISH, 2014;MARQUES, et al, 2019), que envolvem a racionalização de unidades e funções. Já os 'processos do conhecimento' envolvem aquisição, conversão, aplicação e proteção do conhecimento da organização (PARK; HOWARD; GOMULYA, 2018;THALMANN;SARIGIANNI, 2016;BISCOTTI;D'AMICO;MONGE, 2018).…”
Section: Gestão Do Conhecimentounclassified